Pengembangan Instrumen Literasi Numerasi Biologi Pada Pembelajaran IPA Dalam Materi Sistem Pernapasan Pada Manusia - Qisthi, Chairul Umam; Abidin, Zaenal; Sulistyono, Sulistyono (Peneliti.net, 2023)
Minimum Competency Assessment (AKM) which is in line with 21st century skills that require students to be able to keep up with the times, but AKM has serious weaknesses, namely, a discrepancy between what is taught and what is assessed, so teachers should be able to work around these things this is for the smooth running of students in working on AKM questions by familiarizing students with questions based on numeracy literacy and in accordance with the context being taught, based on observations obtained an explanation that students seem less able to follow when faced with material that combines literacy and numeracy, In this regard, research on the development of biological numeracy literacy instruments in science learning in the subject of the respiratory system in humans is very important to do. This research is a development type research using the Research and Development (R&D) research method. The research design used is the ADDIE model research design (Analysis, Design, Development, Implementation, Evaluate). The results obtained for the development of the instrument are in accordance with the stages of the ADDIE model research design, the feasibility of the instrument which is classified as valid and reliable, and has a level of difficulty from easy to difficult categories and item discrimination from less to good categories and there are differences in terms of functionality. The conclusion of the instrument developed is feasible to use to familiarize students with questions based on numeracy literacy and according to the context that is being taught to improve students' numeracy literacy skills.